2015
DOI: 10.1105/tpc.15.00122
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Differential Gene Expression and Epistasis to Discover Candidate Genes for Drought-Associated QTLs in Arabidopsis thaliana

Abstract: Soil water availability represents one of the most important selective agents for plants in nature and the single greatest abiotic determinant of agricultural productivity, yet the genetic bases of drought acclimation responses remain poorly understood. Here, we developed a systems-genetic approach to characterize quantitative trait loci (QTLs), physiological traits and genes that affect responses to soil moisture deficit in the TSUxKAS mapping population of Arabidopsis thaliana. To determine the effects of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 87 publications
2
39
0
Order By: Relevance
“…However, there is extensive evidence for genetic variation in the organelles altering adaptive phenotypes and interacting with nuclear loci (Greiner and Bock, 2013). Recent populations have been developed that are allowing quantitative assessment of the role of genetic variation in the organelle in quantitative phenotypes (McKay et al, 2008;Lovell et al, 2015). Analyzing metabolomic variation in the Arabidopsis Kas 3 Tsu population showed that genomic variation within the organelle altered the accumulation of nearly all metabolites (Joseph et al, 2013a(Joseph et al, , 2013b.…”
Section: Epistasis: Genotype 3 Genotype and Genome 3 Genome Interactionsmentioning
confidence: 99%
“…However, there is extensive evidence for genetic variation in the organelles altering adaptive phenotypes and interacting with nuclear loci (Greiner and Bock, 2013). Recent populations have been developed that are allowing quantitative assessment of the role of genetic variation in the organelle in quantitative phenotypes (McKay et al, 2008;Lovell et al, 2015). Analyzing metabolomic variation in the Arabidopsis Kas 3 Tsu population showed that genomic variation within the organelle altered the accumulation of nearly all metabolites (Joseph et al, 2013a(Joseph et al, , 2013b.…”
Section: Epistasis: Genotype 3 Genotype and Genome 3 Genome Interactionsmentioning
confidence: 99%
“…5B)-DREBs are the most extensively studied drought-responsive group of genes in Arabidopsis (Sakuma et al 2002;Agarwal et al 2006;Xianjun et al 2011); (3) FT, a central gene in the flowering pathway (Fig. 5C)-several recent studies have implicated a physiological and genetic tie between drought-responsive and flowering pathways (McKay et al 2003;Lovell et al 2013Lovell et al , 2015Riboni et al 2013;Kimura et al 2015); (4) RLK1, the rice ortholog (OsLecRK4) which improves resistance to insect herbivory (Liu et al 2015), and (5) a rice ortholog (OSMate2) of the MATE efflux family gene AT1G71140, which, when overexpressed in A. thaliana, alters a variety of abiotic and biotic stress responses (Tiwari et al 2014). …”
Section: Trans and Trans-by-treatment Expression Regulatory Divergencementioning
confidence: 99%
“…Although some studies have reported significant effects of cytonuclear epistasis (17,20,21,23,25), others have found additive cytoplasmic effects but with weak or no cytonuclear epistasis (22). Each of these studies (with the exception of ref.…”
mentioning
confidence: 99%